2012
DOI: 10.1111/j.1365-2966.2011.20358.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of X-ray cavities in the brightest galaxy in the Draco constellation NGC 6338

Abstract: We present results based on the systematic analysis of currently available Chandra archive data on the brightest galaxy in the Draco constellation, NGC 6338, in order to investigate the properties of the X‐ray cavities. In the central ∼6 kpc, at least two, possibly three, X‐ray cavities are evident. All these cavities are roughly of ellipsoidal shape and show a decrement in surface brightness of several tens of per cent. In addition to these cavities, a set of X‐ray bright filaments are also noticed which are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 43 publications
(88 reference statements)
3
53
0
Order By: Relevance
“…The evidences for the presence of such cavities were first reported from the ROSAT observations of Perseus cluster (Boehringer et al 1993). The availability of high quality data from Chandra observations of clusters and groups made it possible to detect many such cases and study their interaction with the ICM in detail (McNamara et al 2000;Fabian et al 2000;Sanders & Fabian 2002;Rafferty et al 2006;Fabian et al 2006;Bîrzan et al 2008;Dong et al 2010;Dunn et al 2010;O'Sullivan et al 2011;David et al 2009;Gitti et al 2012;Pandge et al 2013Pandge et al , 2012Sonkamble et al 2015;Vagshette et al 2016). Radio observations of several such clusters revealed that these cavities spatially match with the radio lobes and are filled with non-thermal gas consisting of relativistic particles and magnetic field (McNamara & Nulsen 2007;Gitti et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidences for the presence of such cavities were first reported from the ROSAT observations of Perseus cluster (Boehringer et al 1993). The availability of high quality data from Chandra observations of clusters and groups made it possible to detect many such cases and study their interaction with the ICM in detail (McNamara et al 2000;Fabian et al 2000;Sanders & Fabian 2002;Rafferty et al 2006;Fabian et al 2006;Bîrzan et al 2008;Dong et al 2010;Dunn et al 2010;O'Sullivan et al 2011;David et al 2009;Gitti et al 2012;Pandge et al 2013Pandge et al , 2012Sonkamble et al 2015;Vagshette et al 2016). Radio observations of several such clusters revealed that these cavities spatially match with the radio lobes and are filled with non-thermal gas consisting of relativistic particles and magnetic field (McNamara & Nulsen 2007;Gitti et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that AGN feedback plays an important role in balancing cooling and heating of the ICM (Fabian 1994;McNamara et al 2005;Bîrzan et al 2004;Rafferty et al 2006;Doria et al 2012;Pandge et al 2012;Sonkamble et al 2015;Vagshette et al 2016). Power required to heat the ICM through AGN feedback can be derived by taking the ratio between the total energy required to create cavities in the ICM and the age of the cavity.…”
Section: Cavity Energeticsmentioning
confidence: 99%
“…Over the years the AGN feedback mechanism, mostly by jet-inflated bubbles, has been solidified (e.g., Dong et al 2010;O'Sullivan et al 2011;Farage et al 2012;Gaspari et al 2012a,b;Birzan et al 2011;Gitti et al 2012;Pfrommer 2013). Key to the establishment of the AGN-JFM in cooling flows are the many observations of X-ray deficient bubbles (e.g., Boehringer et al 1993;Fabian et al 2000;McNamara et al 2001;Heinz et al 2002;Forman et al 2007;Wise et al 2007;Baldi et al 2009;David et al 2009;Gastaldello et al 2009;Gitti et al 2010;Blanton et al 2011;David et al 2011;Machacek et al 2011;Randall et al 2011;Doria et al 2012;Pandge et al 2012;Hlavacek-Larrondo et al 2015). Many of these X-ray bipolar structures resemble visible bipolar structures observed in bipolar PNe (see Figs.…”
Section: Jet-inflated Bubblesmentioning
confidence: 99%
“…This feedback mechanism is driven by active galactic nucleus (AGN) jets that inflate X-ray deficient cavities (bubbles; e.g., Dong et al 2010;O'Sullivan et al 2011;Gaspari et al 2012a,b;Gilkis & Soker 2012). Examples of bubbles in cooling flows include Abell 2052 (Blanton et al 2011), NGC 6338 (Pandge et al 2012), NGC 5044 (David et al 2009), and HCG 62 (Gitti et al 2010), among many others.…”
Section: Introductionmentioning
confidence: 99%